Hubungan antara Durasi Penggunaan Suara dengan Permasalahan Suara pada Aktor Teater di Sanggar Teater di Wilayah Kota Surakarta - Forzachita, Priscilla; Gunawan, Gunawan (Politeknik Kesehatan Kemenkes Surakarta, 2024)
Background: An actor is a profession that requires both good vocal range and a quality voice simultaneously. In their workplace, they utilize their voices, which poses a risk of vocal issues such as overuse, potentially leading to voice problems. Persistent voice problems can endanger their professional career. Objectives: Discovering whether there is a correlation between the duration of voice usage and vocal issues among theater actors at the Theater Studio in the Surakarta City Area. Methods: Based on the type of data, this research is a quantitative study and is cross-sectional type. The sampling technique used in this research is purposive sampling with a sample size of 50 respondents. The statistical test employed is the Spearman’s Rank test. Results: The results of the correlation analysis using Spearman's Rank test indicate that the p-value is 0.188 or >0.05. It can be interpreted as accepting H₀ and rejecting Ha, indicating no relationship between the duration of voice use and voice problems in theater actors at the Theater Workshop in the Surakarta City area. Furthermore, the correlation strength (-0.189) is weak with a negative correlation direction, suggesting that the longer the duration of voice use, the smaller the value of voice problems. Conclusion: There is no correlation between the duration of voice usage and voice problems among theater actors at the Theater Studio in the Surakarta City Area. Keyword : Duration of Voice Use, Voice Problems, Theater Actors